Periodistas y desinformación sobre COVID-19 desde el punto de vista médico-científico. Estudio de caso en Azuay, Ecuador - Verdugo León, Édison (2024)
During the COVID-19 pandemic, the importance of journalists disseminating accurate information to counteract misinformation became more evident. This study, conducted in the province of Azuay, Ecuador, investigated how journalists approached medical-scientific content during the initial wave of the pandemic. For this purpose, 10 journalists were interviewed, and the content of 66 health news stories across print, radio, digital, and audiovisual media was analyzed. The findings indicated that, despite the surge in news coverage, journalists exhibited limitations in source selection and knowledge regarding medical and scientific subjects. The study underscored the reliance on political-governmental sources, a lack of fact-checking, and complications inherent in emergency coverage that restricted access to high-quality information. The conclusions emphasize the necessity of training journalists in health and science reporting to enhance their productive routines. Additionally, the study highlights the significance of a more meticulous observation of journalists’ work contexts. The geographical limitation of the study points to the possibility of future research to compare journalistic practices in different contexts, evaluating strengths and weaknesses in education and training.